Antibacterial activity of five Peruvian medicinal plants against Pseudomonas aeruginosa - Ulloa Urizar, Gabriela (2015)
Objective: To evaluate the susceptibility of Pseudomonas aeruginosa (P. aeruginosa) in vitro to the ethanolic extracts obtained from five different Peruvian medicinal plants. Methods: The plants were chopped and soaked in absolute ethanol (1:2, w/v). The antibacterial activity of compounds against P. aeruginosa was evaluated using the cupplate agar diffusion method. Results: The extracts from Maytenus macrocarpa (“Chuchuhuasi”), Dracontium loretense Krause (“Jergon Sacha”), Tabebuia impetiginosa (“Tahuari”), Eucalyptus camaldulensis Dehn (eucalyptus), Uncaria tomentosa (“Uña de gato”) exhibited favorable antibacterial activity against P. aeruginosa. The inhibitory effect of the extracts on the strains of P. aeruginosa tested demonstrated that Tabebuia impetiginosa and Maytenus macrocarpa possess higher antibacterial activity. Conclusions: The results of the present study scientifically validate the inhibitory capacity of the five medicinal plants attributed by their common use in folk medicine and contribute towards the development of new treatment options based on natural products.